PENGARUH STRATEGI DIVERSIFIKASI USAHA TERHADAP KINERJA KEUANGAN DAN NILAI PERUSAHAAN: (STUDI PADA PERUSAHAAN TEKNOLOGI YANG TERDAFTAR BEI 2021-2023 ) - Muhammad Jais; Linda Rahmazaniati; Rimal Mahdani (Politeknik Negeri Ambon, 2026)
Introduction: Research on Indonesia's digital economic growth has encouraged technology companies to implement business diversification strategies as a way to expand revenue streams and spread business risk. However, previous research on the effect of diversification on financial performance and firm value has yielded inconsistent findings and has relatively little focus on the characteristics and dynamics of the technology sector. Methods: This study aims to analyze the effect of business diversification strategy (1-HHI) on financial performance (ROA) and firm value (Tobin's Q) using a quantitative approach with panel data regression (random effect model). The sample includes 26 technology companies listed on the Indonesia Stock Exchange (IDX), selected through purposive sampling for the 2021-2023 period.Results: The results show that diversification has a positive effect on ROA and a negative effect on Tobin's Q. However, the business diversification strategy has not significantly contributed to the financial performance or value of technology companies during the observation period. This is reflected in the relatively low coefficient of determination (R²), indicating that variations in ROA and Tobin's Q are only partially explained by business diversification, while other fundamental factors are more dominant.Conclusion and suggestion: Therefore, companies are advised to focus their strategies on strengthening core business synergies and operational efficiency. At the same time, investors need to consider other fundamental indicators in assessing investment prospects. Keywords: Business Diversification Strategy, Financial Performance, Firm Value, ROA, Tobin’s Q, Technology Companies.